Why Do They Select Medical Profession? - A Study of Students’ Perceptions - Shukla, Aparajita; Sheth, Jay K; Patel, Kirti (National Journal of Community Medicine, 2017)
Background: Like any profession, reasons for selecting medical profession can vary and may have an impact on achieving professional goals. The study conducted to analyze reasons for selecting medical profession as perceived by students at the time of joining medical college and trend over a decade. Methodology: Within 10 days of joining, students’ ranked 10 common reasons for selecting Medical profession. Data of three batches (2001, 2006 and 2011) was analyzed for preferences, ranking order and change in pattern, if any. Results: Total 425 completed records were analyzed and top 3 reasons were analyzed in depth. “Subject of own interest (OI)” was their first choice (8.45 & 8.80) which went down to second choice (7.18) in 2011. “For serving the society (SS)” moved upward in the rank from third to first position (6.43, 6.75, 7.20). “Highly respected profession (RP)” as a reason went down from 2nd, 3rd to 4th place. (6.54, 6.58, 6.22). In 2011, “parents’ desire (PD)” was ranked third (7.0), selection being significantly higher by male students (p=0.008). In 2001, NRI group ranked RP significantly higher (p=0.034) and students with doctor parents also ranked it higher (p=0.017). Conclusions: “Serving the society” as a reason for entering medical profession shifted from 3rd to 1st position over 10 years. “Desire of parents” became more important with time. “Highly respected profession” seems to have lost importance!